Use of Platelet Rich Plasma in Urological Conditions - Agnieszka Mioskowska; Joanna Szydziak; Aleksandra Hrapkowicz; Kinga Janowska; Daria Dąbkowska; Olga Szeidl; Dominka Rehan; Julia Wołoszczak (Kazimierz Wielki University, 2024)
Introduction: Platelet-rich plasma (PRP) has become an increasingly popular therapeutic tool across various medical specialties since its introduction in 1958. Defined as a concentrated solution of platelets and growth factors derived from autologous blood, PRP supports tissue repair and regeneration processes. PRP's composition includes high concentrations of platelets and growth factors that facilitate angiogenesis, connective tissue remodeling, and cellular repair, making PRP a promising treatment option for complex urological conditions and beyond. Purpose of the study: This review aims to summarize the applications and efficacy of PRP in treating specific urological conditions such as erectile dysfunction, Peyronie's disease, urethral stricture, hypospadias, interstitial cystitis and urinary incontinence. Materials and Methods: To provide a comprehensive summary of current knowledge on this topic, a literature review of English-language articles, with an emphasis on recent publications, was conducted. The review utilized the PubMed database and included 51 studies accessed prior to October 2024. Conclusions: PRP therapy appears to be a promising, safe, and minimally invasive treatment option for several urological conditions. Studies suggest that PRP may benefit erectile function, reduce symptoms in Peyronie's disease, and improve outcomes in conditions related to the urethra and bladder, with minimal reported adverse effects. However, the lack of standardized PRP preparation protocols and large placebo-controlled trials poses a challenge to fully establishing its efficacy. Further research is necessary to confirm PRP's effectiveness, optimize preparation and administration methods, and develop guidelines for its clinical application in urology.